Bunga Bank Dalam Tinjauan Fikih Dan Maqashid Syariah - Ahmad Yusdi Gozaly; Premi Anggraini Premi (IQTISHOD: Jurnal Pemikiran dan Hukum Ekonomi Syariah, 2024)
This study aims to examine bank interest in the review of fiqh and maqashid syariah in order to see bank interest from the point of view of maslahat and madharat which is the main purpose of Islamic sharia. The study used qualitative descriptive methods with the type of library research to examine scholars' opinions about usury and bank interest contained in scholarly books and other literature. The results showed that bank interest is closely related to maqashid dharuriyyah in guarding property (hifzhul mal) and guarding the soul (hifzhul nafs). There are 2 (two) different points of view about the 'illah (cause) of the haram of riba also causes differences of opinion about the legal status of interest in banking. According to scholars who declare bank interest haram, 'illah (cause) riba forbidden is ziyadah (addition) in loans regardless of the amount, so bank interest is punished haram because the system used by conventional banks always has an increase in principal in loans and deposits. While scholars who allow interest assume that the reason for riba is not just ziyadah, but ziyadah containing dzulm (tyranny).